PENGARUH AKULTURASI DALAM PROSES INTERAKSI ANTARBUDAYA TERHADAP KESADARAN BUDAYA BERBAHASA DAERAH SETEMPAT BAGI MAHASISWA RANTAU - A. Dian Fitriana (KOMUNIDA : Media Komunikasi dan Dakwah, 2018)
a communication process or intercultural interaction, an immigrant conducts some activities as a self- adaptation to the local culture called acculturation. The adaptation is supported by the cultural awareness of local language that becomes the supporting factor. The research was aimed at finding out how big the influence of acculturation consisting of personal communication, social communication, communication environment, and acculturation potential toward the awareness of language culture involving knowledge, attitude, and behavior. The research used the quantitative method with the Path Analysis approach. The sampling technique used was Disproportional Stratified sampling. The data were obtained through questionnaires, interview, observation, and documentary study. The result of the research shows that there was significant influence of personal and social communication in the intercultural interaction process toward the cultural awareness of local language among the South Sulawesi students in Bandung, shown by the percentage of each factor which was: 36.8 % and 48.6 %. The research also showed that there was no significant influence of communication environment and acculturation potential in the intercultural interaction process toward the cultural awareness of local language among the South Sulawesi students in Bandung shown by the percentage of 13.3 % and 1.3 %.